Cytoskeleton Dynamics in Peripheral T Cell Lymphomas: An Intricate Network Sustaining Lymphomagenesis - Fragliasso, Valentina; Tameni, Annalisa; Inghirami, Giorgio; Mularoni, Valentina; Ciarrocchi, Alessia (Frontiers in Oncology, 2021)
Defects in cytoskeleton functions support tumorigenesis fostering an aberrant proliferation and promoting inappropriate migratory and invasive features. The link between cytoskeleton and tumor features has been extensively investigated in solid tumors. However, the emerging genetic and molecular landscape of Peripheral T Cell Lymphomas (PTCL) has unveiled several alterations targeting structure and function of the cytoskeleton, highlighting its role in cell shape changes and the aberrant cell division of malignant T cells. In this review, we summarize the most recent evidence about the role of cytoskeleton in PTCLs development and progression. We also discuss how aberrant signaling pathways, like JAK/STAT3, NPM-ALK, RhoGTPase and Aurora Kinase, can contribute to lymphomagenesis by modifying the structure and the signaling properties of cytoskeleton.